The straw, the brick, and the metaphor: in the narratives in the Book of Exodus - Jędraszek , Sławomir (Acta Archaeologica Lodziensia, 2023)
Mud-brick, widely used in Egyptian architecture, became one of the symbols of the hard labour of the Israelites in ancient Egypt, assuming the metaphorical significance in the biblical narrative recounting the events related to the Exodus. The resulting text refers specifically to this category of building material and its metaphorical, symbolic meaning.